Short DNA Fragments without Sequence Similarity Are Initiation Sites for Replication in the Chromosome of the Yeast Yarrowia lipolytica - Vernis, Laurence (The American Society for Cell Biology, 1999)
We have previously shown that both a centromere (CEN) and a replication origin are necessary for plasmid maintenance in the yeast Yarrowia lipolytica (Vernis et al., 1997). Because of this requirement, only a small number of centromere-proximal replication origins have been isolated from Yarrowia. We used a CEN-based plasmid to obtain noncentromeric origins, and several new fragments, some unique and some repetitive sequences, were isolated. Some of them were analyzed by two-dimensional gel electrophoresis and correspond to actual sites of initiation (ORI) on the chromosome. We observed that a 125-bp fragment is sufficient for a functional ORI on plasmid, and that chromosomal origins moved to ectopic sites on the chromosome continue to act as initiation sites. These Yarrowia origins share an 8-bp motif, which is not essential for origin function on plasmids. The Yarrowia origins do not display any obvious common structural features, like bent DNA or DNA unwinding elements, generally present at or near eukaryotic replication origins. Y. lipolytica origins thus share features of those in the unicellular Saccharomyces cerevisiae and in multicellular eukaryotes: they are discrete and short genetic elements without sequence similarity.